Correlation function determination for inhomogeneities scattering an acoustic wave - LEWANDOWSKI, Józef (Archives of Acoustics, 1978)
A random inhomogeneous isotropic medium filling a domain immersed in an infinitely extended homogeneous isotropic medium is considered. The formulae describing the scalar potential of the scattered field are deduced for small and large distances from the domain of the heterogeneous material. The fluctuations of density and wave propagation velocity (and also pressure in the case of a nonviscous emulsion) are treated as random variables of the space coordinates. The correlation function is calculated from the appropriate farfield solution and expressed in terms of a scalar potential for the angular distribution of the scattered wave. This general method is adapted for a non-viscous random emulsion and the correlation function is expressed in terms of the intensity angular distribution of the scattered wave.